Integrated Treatment of Substance Use and Psychiatric Disorders - Kelly, Thomas M. (2013)
Epidemiological studies find that psychiatric disorders, including mental disorders and substance use disorders, are common among adults and highly comorbid. Integrated treatment refers to the focus of treatment on two or more conditions and to the use of multiple treatments such as the combination of psychotherapy and pharmacotherapy. Integrated treatment for comorbidity has been found to be consistently superior compared to treatment of individual disorders with separate treatment plans. This article focuses on a review of the risks for developing comorbid disorders and the combinations of treatments that appear to be most effective for clients with particular comorbid disorders.